2019
DOI: 10.1029/2018rg000619
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Classical Observations in Hydrogeology: The Advantages of Including Exchange Flux, Temperature, Tracer Concentration, Residence Time, and Soil Moisture Observations in Groundwater Model Calibration

Abstract: Traditionally, groundwater and surface water flow models have been calibrated against two observation types: hydraulic heads and surface water discharge. It has repeatedly been demonstrated, however, that these classical observations do not contain sufficient information to calibrate flow models. To reduce the predictive uncertainty of flow models, the consideration of other observation types constitutes a promising way forward. Despite the ever-increasing availability of other observation types, however, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 167 publications
(372 reference statements)
2
89
0
Order By: Relevance
“…This study explores the ramifications of assimilating tritium concentration and tritium-derived interpretation observations, specifically in the context of two examples of decision-support modeling. The benefit or otherwise of tritium data in other contexts such as site system characterization and understanding and conceptual-model development is therefore not the focus of the current study; this study is concerned with a model's ability to "predict" (in two decision-support contexts) rather than "explain" (observed system behavior), as contrasted by Shmueli (2010).…”
Section: Resultsmentioning
confidence: 99%
“…This study explores the ramifications of assimilating tritium concentration and tritium-derived interpretation observations, specifically in the context of two examples of decision-support modeling. The benefit or otherwise of tritium data in other contexts such as site system characterization and understanding and conceptual-model development is therefore not the focus of the current study; this study is concerned with a model's ability to "predict" (in two decision-support contexts) rather than "explain" (observed system behavior), as contrasted by Shmueli (2010).…”
Section: Resultsmentioning
confidence: 99%
“…They reported that, overall, tracer data were of considerable benefit in terms of forecast uncertainty reduction. In a recent review paper, Schilling et al (2019) state that assimilation of concentration observations through surface water/groundwater flow model history matching "harbors huge potential", based on the findings of previous studies, while assimilation of tracer-derived residence time observations in these models also often help significantly (where an appropriate approach is adopted, e.g., Sanford (2011); Zuber et al (2011)).…”
Section: Introductionmentioning
confidence: 99%
“…The calibration was performed automatically for groundwater flow and manually for the heat transport parameters. It is generally good practice to calibrate groundwater flow and heat transport parameters together in order to reduce uncertainties related to ill-posed models, especially with models developed in heterogeneous hydrogeological environments [64,75,76]. Due to its highly time-consuming aspect, performing a transient groundwater flow and heat transfer model calibration was hardly feasible; but not doing so bears inherent uncertainties [64].…”
Section: Discussionmentioning
confidence: 99%
“…A combined flow and transport calibration would have provided a more robust model but with a level of detail that would not likely be significant compared to the scale of the study area. Applying homogeneous transport parameters to the model domain based on local scale calibrated parameters between O1 and W2 imposes the unique character of these parameters and details on heterogeneous materials are lost [71,76,77]. Extensive datasets collected in all the wells by carrying out several heat and solute tracer tests would have helped to better characterize the aquifer [68].…”
Section: Discussionmentioning
confidence: 99%